2021
DOI: 10.1186/s12967-021-03103-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the spatial–temporal specific theca cell Cyp17 overexpression on the reproductive phenotype of the novel TC17 mouse

Abstract: Background In the ovarian follicle, the Theca Cells (TCs) have two main functions: preserving morphological integrity and, importantly, secreting steroid androgen hormones. TCs express the essential enzyme 17α-hydroxylase/17,20-desmolase (CYP17), which permits the conversion of pregnenolone and progesterone into androgens. Dysregulation of CYP17 enzyme activity due to an intrinsic ovarian defect is hypothesized to be a cause of hyperandrogenism in women. Androgen excess is observed in women wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 92 publications
(71 reference statements)
0
5
0
Order By: Relevance
“…Similarly, Woodruff and Shea [48] showed that abnormal follicles in the stiff ECM produce a higher-than-normal ratio of androgen to estrogen, indicating inadequate steroid conversion. In addition, Secchi et al [52] . applied RNA-seq analysis to identify the perturbed ECM and steroid synthesis pathways by constructing mouse models of elevated testosterone levels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Woodruff and Shea [48] showed that abnormal follicles in the stiff ECM produce a higher-than-normal ratio of androgen to estrogen, indicating inadequate steroid conversion. In addition, Secchi et al [52] . applied RNA-seq analysis to identify the perturbed ECM and steroid synthesis pathways by constructing mouse models of elevated testosterone levels.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Woodruff and Shea [48] showed that abnormal follicles in the stiff ECM produce a higher-than-normal ratio of androgen to estrogen, indicating inadequate steroid conversion. In addition, Secchi et al [52] applied RNA-seq analysis to identify the perturbed ECM and steroid synthesis pathways by constructing mouse models of elevated testosterone levels. Therefore, we speculate that the androgen surplus in PCOS patients disturbs the delicate balance among hormones, and it is crucial in ovarian cortex alteration, especially ECM remodeling.…”
Section: Influence Of Mechanical Stress On Primordial Follicle Activa...mentioning
confidence: 99%
“…Interestingly, this model also displayed the PCOS-like traits of hyperandrogenism and oligoovulation. Thus, the increase in the stroma in this model could potentially be due to an increase in AR-mediated actions due to the increased androgen production (Secchi et al 2021).…”
Section: Location Of Androgenic Target Sites In Pcos Pathogenesismentioning
confidence: 96%
“…Additionally, investigations into the potential role of the ovarian stroma are warranted as women with PCOS have an increased volume of ovarian stroma, and more structural collagen and AR are expressed in the fetal stroma (Fowler et al 2011). Recently, in a novel transgenic mouse model overexpressing CYP17 only in thecal cells, the development of hypertrophic stromal cells was attributed to the enrichment of pathways for collagenisation and extracellular matrix organisation (Secchi et al 2021). Interestingly, this model also displayed the PCOS-like traits of hyperandrogenism and oligoovulation.…”
Section: Location Of Androgenic Target Sites In Pcos Pathogenesismentioning
confidence: 99%
“…TC17 mice had ovarian features similar to trans men including impaired folliculogenesis. These mice will be valuable tool for studying the effects of Cyp17 overexpression and hyperandrogenism in the ovary Secchi et al 2021 [ 131 ] Rat Wistar Feminising To assess the effects of E2 ethanate (E2EN) and dihydroxyprogresterone acetophenide (DHPA) on metabolic and renal outcomes in male-to-female rats GAHT combined with E2EN/DHPA produced a feminising change in male rats without altering blood pressure and renal adaptations appeared closer to female controls Gusmão-Silva et al 2022 [ 132 ] Mice C57BL/6 J Masculinising To determine the effects and mechanisms of long-term T treatment on cardiovascular function in female-to-male mice The vascular dysfunction observed in female-to-male mice following T treatment is mediated via a T-cell/IL-17R-dependent mechanism Santos et al 2022 [ 133 ] Mice C57BL/6 J Masculinising To determine the effect of GAHT on wound healing in female-to-male mice T inhibits cutaneous wound healing in female-to-male mice and is characterised by increased mRNA expression of inflammatory cytokines, TNFα concentrations and macrophage proliferation in the wound Reiche et al 2022 [ 134 ] Mouse C57BL/6N Puberty Suppression Masculinising To develop a female-to-male mouse model of pubertal suppression and GAHT One of the first models to mirror female-to-male transition in adolescence using GNRHa treatment followed by T therapy Cruz et al 2022 [ 135 ] Rat Sprague–Dawley Masculinising and feminising To establish dosing regimens and to identify biomarkers of transition for future preclinical models of transgender health The sex-specific expression of CYP450 was suggested as a suitable biomarker to guide appropriate masculinising and feminising GAHT in preclinical models of transition Tassinari et al 2023 [ 136 ] Abbreviation: Ovx , ovariectomy; HPG , hypothalamic pituitary gonadal; GnRHa , gonadotropin receptor hormone agonist; T , testosterone; E2 , estradiol; Veh , vehicle; wks , weeks; CA , cyproterone acetate; eCG , equine chorionic gonadotropin; hCG , human chorionic gonadotropin; APOE , apolipoprotein E; CYP17 , 17α...…”
Section: Preclinical Mouse Models Of Transgender Healthmentioning
confidence: 99%